STUDY THE PREVALENCE OF HEPATITIS B SURFACE ANTIGEN AND ITS ASSOCIATED FACTORS IN THE POPULATION OF KACHIPURA (INDIA) - WADEKAR, TINA; HIRAPURE, PRADIP; PARANJAPE, SHWETA; UPADHYE, VIJAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Hepatitis B virus infection (HBV) is a global public health problem. Nearly two billion people in the world have been acutely infected by HBV and there are nearly 350 million people chronically infected with HBV. In this research study Population based hepatitis survey was carried out to estimate sero-prevalence of hepatitis B virus (HBV) infection for the Kachipura population which is located in Nagpur Dharampeth area (India). Random sampling of population has been done. Oral consent was taken before taking blood sample. The selected population could answer the questionnaire. All age group people are selected for sampling. Prevalence of hepatitis B surface antigen and its associated factors in Kachipura population has been studied. Also study the relation between hepatitis B positive and various symptomatic characteristics. Effect of various risk factor like drug abuse, food habits have been studied. Blood samples were taken and serological analysis of collected blood samples has been done using HBsAg kit. Data were analyzed using standard biostatistician tool and software SPSS. 1.86% of prevalence rate of hepatitis B viral infection has been found in the population of Kachipura. Relation between blood groups and HBsAg positive has been found that the people with ORh+ve blood group are very prone to Hepatitis B infection.